Dysregulation of coagulation in cerebral malaria - Moxon, Christopher Alan (Elsevier/North-Holland Biomedical Press, 2009)
Cerebral malaria (CM) is a life-threatening complication of Plasmodium falciparum infection and represents a major cause of morbidity and mortality worldwide. The nature of the pathogenetic processes leading to the cerebral complications remains poorly understood. It has recently emerged that in addition to their conventional role in the regulation of haemostasis, coagulation factors have an inflammatory role that is pivotal in the pathogenesis of a number of acute and chronic conditions, including CM. This new insight offers important therapeutic potential. This review explores the clinical, histological and molecular evidence for the dysregulation of the coagulation system in CM, looking at possible underlying mechanisms. We discuss areas for future research to improve understanding of CM pathogenesis and for the development of new therapeutic approaches.